Palmar Creases and Their Implication on Carpal Tunnel Surgery. (June 2022) - Mujadzic, Tarik; Friedman, Harold I.; Atwez, Abdelaziz; Botonjic, Hata; Mujadzic, Mirza M.; Chen, Elliott; Gilstrap, Jarom N.; Mujadzic, Mirsad M.
Abstract : Background: A thorough knowledge of normal and variant anatomy of the wrist and hand is fundamental to avoiding complications during carpal tunnel release. The purpose of this study was to document variations of the surface anatomy of the hand to identify a safe zone in which the initial carpal tunnel incision could be placed. The safe zone was identified as the distance between the radial side of hook of hamate and the ulnar edge of the origin of the motor branch of the median nerve (MBMN). Methods: Kaplan's cardinal line and other superficial markers were used to estimate the size of the safe zone, in accordance to prior published anatomical studies. The presence of a longitudinal palmar crease (thenar, median, or ulnar creases) within the safe zone was recorded. Results: Of the 150 participants (75 male, 75 female) examined, the average safe zone widths were 10.85 (right) and 10.28 (left) mm. In all the hands examined, 86.33% of the safe zones (259 of 300) contained a longitudinal palmar crease. In the White population (n = 50), the average safe zone widths were 11.49 (right) and 10.01 (left) mm; in the African American population (n = 50), the average safe zone widths were 12.27 (right) and 12.01 (left) mm; and in the Asian population (n = 50), the average safe zone widths were 8.79 (right) and 8.82 (left) mm. On overage, males had a larger safe zone width than females by 4.55 mm. Conclusions: Although there seems to be variability between race and sex with regard to safe zone width, finding 86.33% of longitudinal palmar creases within the safe zone suggests that, for most patients, the initial carpal tunnel surgery incision may be hidden within the palmar crease while minimizing the risk of motor branch of the median nerve injury. Overall, the safe zone width is on average up to 10.5 mm measured from the hook of the hamate along Kaplan's cardinal line.